Enhancing Hydropower Management through Artificial Intelligence: Insights from Norway's Experience - Jeroen, Claude; Pettersen, Juzeniene; Hyysalo, Kjesbu (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
Norway is a global leader in renewable energy, with hydropower accounting for 90% of its electricity generation. The country's hydropower sector is crucial to both national and international energy demands, and the need for efficient management has become more pressing as the world shifts from fossil fuels to cleaner energy sources. Artificial Intelligence (AI) is emerging as a powerful tool for optimizing hydropower management by improving predictive analytics, automating decision-making, and processing real-time data. In Norway, AI is increasingly being used to forecast water flow and manage energy production more effectively, while also enhancing predictive maintenance to minimize downtime and operational costs. Despite its potential, the implementation of AI faces challenges such as high costs, infrastructure investments, and data privacy concerns. This article explores recent innovations in AI applied to hydropower in Norway, discussing both the opportunities and challenges. The successful integration of AI into hydropower operations holds promise for improving efficiency and sustainability, offering insights for broader adoption across the global renewable energy sector. Future developments in AI and its application in renewable energy, such as smart grids and interconnecting different energy sources, could further enhance the energy landscape.